Energy dissipation to tungsten surfaces upon hot-atom and Eley-Rideal recombination of H 2 - Galparsoro, Oihana (2018)
Adiabatic and nonadiabatic quasi-classical molecular dynamics simulations are performed to investigate the role of electron-hole pair excitations in hot-atom and Eley-Rideal H 2 recombination mechanisms on H-covered W(100). The influence of the surface structure is analyzed by comparing with previous results for W(110). In the two surfaces, hot-atom abstraction cross sections are drastically reduced due to the efficient energy exchange with electronic excitations at low incident energies and low coverage, while the effect on Eley-Rideal reactivity is negligible. As the coverage increases, the projectile energy is more efficiently dissipated into the other adsorbates. Consequently, the effect of electronic excitations is reduced. As a result, the reactivity and final energy distributions of the formed H 2 molecules are similar for both abstraction mechanisms.